Phytochemical and biochemical studies of wild chervil (Anthriscus sylvestris) - Orčić, Dejan; Berežni, Sanja; Mimica-Dukić, Neda (Biologia Serbica, 2022)
Plants represent important sources of bioactive molecules that can be used directly as medications, or as industrial precursors thereof. Podophyllotoxin, that was first isolated from mayapple (Podophyllum peltatum L.), and related natural and semi-synthetic lignans, are important antiviral, antihelmintic and especially antitumor agents, used in traditional and official medicine. Since the exploitation of common sources, such as Sinopodophyllum hexandrum, becomes unsustainable, new species are being investigated. One of the most promising is wild chervil (Anthriscus sylvestris (L.) Hoffm.), a widely distributed wild-growing Apiaceae species, commonly considered a noxious weed, that is known to be rich in lignans, especially aryltetralins (such as deoxypodophyllotoxin, podophyllotoxin and podophyllotoxone) and dibenzylbutyrolactones (including yatein and nemerosin), but also in various phenylpropanoids and terpenoids. This paper provides an extensive overview of A. sylvestris chemical composition investigations conducted thus far, with special focus on recent comprehensive profiling studies based on hyphenated techniques. Additionally, a detailed account of the bioactivity studies of both extracts and isolated compounds, confirming their antioxidant, anti-inflammatory and antiproliferative activity, is given.